Complete chloroplast genomes of 25 mulberry plants: insight into genome characteristics, comparative analysis and phylogenetic relationships - Jinhong Yang; Wei Jiang; Jiayue Huang; Yunwu Peng; Fang Yang; Weiqing Kong (BMC Genomics)
Abstract Background Mulberry (Morus L.) is an economically important plant with abundant resources distributed around the world. Mulberries now have different breeding directions and uses of leaves or fruits, and additionally wild mulberries in natural environments. The classification of mulberry species is inconsistent, as previous phylogenetic and taxonomic studies using morphological and molecular markers have yielded low resolution. Additionally, the phylogenetic relationships among the three uses haven’t been studied to date. Herein, 25 Morus plants representing the three uses were selected, their chloroplast (cp.) genomes were sequenced and analyzed, including cp. genome structure, features and phylogenetic relationships using cp. genomes and SSR markers. Results The cp. genome sequences of 25 Morus plants were determined to be 159,008–159,346 bp in length, which included a pair of inverted repeats of 25,654, 25,678 or 25,690 bp that separated a large single copy region of 87,912–88,142 bp and a small single copy region of 19,740–19,853 bp. Annotation showed that they contained a total of 129 genes: 84 protein-coding, 37 tRNA and eight rRNA genes. Comparative genomics showed that the cp. sequence among Morus was relatively conserved, while there were still some high variation regions, and SSR loci with length or nucleotide content polymorphism. The phylogenetic trees constructed using maximum likelihood analysis and Bayesian inference method based on the cp. genome sequences, and the Neighbor-Joining dendrogram based on SSRs, all suggested that the species in this study could be distinguished as three clades, consistent with their uses: leaves, fruits and wild mulberries. In addition, some specific SSRs distributed in the clades may be useful for classification and identification of Morus plants. Conclusion This study obtained the cp. genomes of 25 Morus plants and provided the first comparative cp. genome analysis of Morus species categorized by uses, identifying specific SSR markers for classification, which enhanced our comprehension on their classification and phylogenetic relationships.